Exosomes derived from M2 macrophages regulate airway inflammation by modulating epithelial cell proliferation and apoptosis - Yinying Ren; Mi Zhou; Yuehan Li; Yan Li; JinYing Xiang; Fang Deng; Zhengxiu Luo; Enmei Liu; Jinyue Yu; Zhou Fu; Fengxia Ding; Bo Liu (Journal of Inflammation)
Abstract Background Asthma is a chronic inflammatory disease characterized by airway remodeling and immune dysregulation. This study aimed to explore the mechanisms by which M2 macrophage-derived exosomes (M2Φ-Exos) regulate airway inflammation in asthma by modulating epithelial cell proliferation and apoptosis. Methods M2Φ-Exos were extracted and characterized by morphology, size, and marker protein expression. In vitro, the effects of M2Φ-Exos on House Dust Mites (HDM)-stimulated mouse lung epithelial cells (MLE-12s) were evaluated using western blotting to analyze Proliferating Cell Nuclear Antigen (PCNA), B-cell lymphoma-2 (Bcl-2), Bcl-2-associated X protein (Bax), and cleaved caspase-3 expression. In vivo, M2Φ-Exos were administered to HDM-induced asthmatic mice to assess their impact on airway inflammation, epithelial remodeling, and proliferation-apoptosis balance using immunohistochemistry, immunofluorescence, and western blotting. Cytokine levels in lung tissue and bronchoalveolar lavage fluid (BALF) were measured by qRT-PCR and ELISA. Results M2Φ-Exos displayed typical cup-shaped morphology, an average diameter of 115.5 nm, and expressed marker proteins CD9, TSG101, and CD63. MLE-12 cells internalized M2Φ-Exos, leading to reduced abnormal proliferation and apoptosis in HDM-stimulated cells. In asthmatic mice, M2Φ-Exos alleviated airway inflammation and epithelial thickening while reducing PCNA, cleaved caspase-3, and Bax levels and increasing Bcl-2 expression. M2Φ-Exos suppressed pro-inflammatory cytokines (IL-4, IL-5, IL-13) and Transforming growth factor (TGF)-β, while enhancing anti-inflammatory cytokine IFN-γ and IL-10. Conclusion These findings demonstrate that M2Φ-Exos regulate the imbalance in epithelial proliferation and apoptosis in asthma, reducing inflammation and mitigating tissue remodeling, and provide new insights into potential therapeutic strategies for asthma management.